Leading the Green Revolution: How Transformational and Green Servant Leadership Drive Employee Sustainability in Hospitality and Tourism Industry - Osama Ahmed; Sadia Javed; Einas Azher; Bushra Jabbar; Farrukh Zafar (Indus Journal of Social Sciences, 2025)
The worldwide organizational focus on sustainability requires leadership methods that encourage employees to adopt environmentally responsible behaviors. The research investigates how Green Transformational Leadership (GTFL) combined with Green Servant Leadership (GSL) affects Employee Green Performance (EGP) through Green Work Engagement (GWE) mediation and Environmental Awareness (EA) moderation. This study collected data from hospitality and tourism sector employees in Karachi, Pakistan through a quantitative research method and then analyzed it using Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS. The analysis demonstrates that Green Transformational Leadership together with Green Servant Leadership positively influences Employee Green Performance via Green Work Engagement which serves as a critical mediator. The research demonstrates Environmental Awareness enhances the connection between Green Work Engagement and Employee Green Performance which shows sustainability knowledge is vital for promoting green behaviors at work. The research enriches the current body of work by merging leadership principles, employee engagement methods and environmental awareness into a comprehensive sustainability framework which delivers significant knowledge for executives, HR specialists and government officials. Research findings recommend organizations implement dual leadership methods alongside Green HRM practices and environmental awareness training while taking advantage of technology-based sustainability initiatives to improve sustainability results. The research points out that including sustainability within corporate leadership strategies and employee programs can build an environmentally responsible workforce. Upcoming investigations need to evaluate supplementary mediating and moderating factors while performing cross-industry studies and longitudinal research to strengthen insights into sustainability-focused leadership and environmentally responsible employee behavior.